2016
DOI: 10.1111/1755-0998.12501
|View full text |Cite
|
Sign up to set email alerts
|

Using occupancy modelling to compare environmental DNA to traditional field methods for regional‐scale monitoring of an endangered aquatic species

Abstract: Environmental DNA (eDNA) monitoring approaches promise to greatly improve detection of rare, endangered and invasive species in comparison with traditional field approaches. Herein, eDNA approaches and traditional seining methods were applied at 29 research locations to compare method-specific estimates of detection and occupancy probabilities for endangered tidewater goby (Eucyclogobius newberryi). At each location, multiple paired seine hauls and water samples for eDNA analysis were taken, ranging from two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 57 publications
(153 reference statements)
7
136
2
Order By: Relevance
“…Our results are consistent with Spear et al (2015), who found that eDNA sampling outperformed conventional surveys for hellbenders. Furthermore, our results are consistent with other eDNA studies that report higher detection estimates than conventional sampling methods (Eiler, Löfgren, Hjerne, Nordén, & Saetre, 2018;Jane et al, 2015;Schmelzle & Kinziger, 2016;Schmidt, Kery, Ursenbacher, Hyman, & Collins, 2013). Estimating detection probabilities from multiple site visits accounts for false negatives (i.e., when the animal is present at a site but goes undetected; MacKenzie et al, 2002).…”
Section: Detection Probabilitiessupporting
confidence: 89%
See 2 more Smart Citations
“…Our results are consistent with Spear et al (2015), who found that eDNA sampling outperformed conventional surveys for hellbenders. Furthermore, our results are consistent with other eDNA studies that report higher detection estimates than conventional sampling methods (Eiler, Löfgren, Hjerne, Nordén, & Saetre, 2018;Jane et al, 2015;Schmelzle & Kinziger, 2016;Schmidt, Kery, Ursenbacher, Hyman, & Collins, 2013). Estimating detection probabilities from multiple site visits accounts for false negatives (i.e., when the animal is present at a site but goes undetected; MacKenzie et al, 2002).…”
Section: Detection Probabilitiessupporting
confidence: 89%
“…Previous studies have indicated a relationship between eDNA concentrations and animal abundance or biomass Klymus, Richter, Chapman, & Paukert, 2015;Pilliod et al, 2013;Schmelzle & Kinziger, 2016;Takahara, Minamoto, Yamanaka, Doi, & Kawabata, 2012;Thomsen et al, 2012). Previous studies have indicated a relationship between eDNA concentrations and animal abundance or biomass Klymus, Richter, Chapman, & Paukert, 2015;Pilliod et al, 2013;Schmelzle & Kinziger, 2016;Takahara, Minamoto, Yamanaka, Doi, & Kawabata, 2012;Thomsen et al, 2012).…”
Section: Comparing Edna Concentration and Cpuementioning
confidence: 99%
See 1 more Smart Citation
“…Site occupancy detection models (SODMs), which provide an estimate of the number of occupied sites whilst accounting for imperfect detection, have been suggested as one way to overcome the issue of imperfect detection in eDNA studies (Hunter et al., ; Lahoz‐Monfort, Guillera‐Arroita, & Tingley, ; Moyer, Diaz‐Ferguson, Hill, & Shea, ; Schmelzle & Kinziger, ; Schmidt et al., ). For example, Schmidt et al.…”
Section: Introductionmentioning
confidence: 99%
“…They do not address the question of whether positive BC or SC eDNA samples indicate the presence of AC in the CAWS and other sampling locations near the Great Lakes. Occupancy models are used to estimate the probability of target species presence using eDNA sampling results by modelling the probability of detection and amplification (Erickson et al, ; Mize et al, ; Schmelzle & Kinziger, ; Willoughby et al, ). The model in this paper could be incorporated within an occupancy modelling framework by detailing the uncertainties in the detection and amplification steps.…”
Section: Discussionmentioning
confidence: 99%